Religious themes in contemporary comics: between indoctrination and creative interpretation - Jaworski, Marcin (Człowiek i Społeczeństwo, 2016)
In today’s world, popular culture is an identity-building experience, a powerful driver of social belonging and a domain of emotional involvement. It is a mirror of sorts that reflects human needs and desires – including religious ones. This paper discusses a number of pop cultural texts (comic books) that explore religious themes, and attempts to examine the nature and “quality” of these explorations. In other words, this paper seeks to determine which of these comic books propose a superficial or trivial treatment of religious traditions, and which graphic novels deserve to be considered as culturally relevant, even if perhaps not entirely orthodox, pieces of artwork. A broad methodological approach was applied, with a wide variety of proposals being discussed: on the one hand it examines comic books used as a mere tool for “ideological” persuasion, whilst on the other it looks into comic books that explore religious themes while treating them as a resonant cultural resource.